2007
DOI: 10.1093/heapro/dam001
|View full text |Cite
|
Sign up to set email alerts
|

Growing urban health: Community gardening in South-East Toronto

Abstract: This article describes results from an investigation of the health impacts of community gardening, using Toronto, Ontario as a case study. According to community members and local service organizations, these gardens have a number of positive health benefits. However, few studies have explicitly focused on the health impacts of community gardens, and many of those did not ask community gardeners directly about their experiences in community gardening. This article sets out to fill this gap by describing the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
385
1
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(413 citation statements)
references
References 13 publications
15
385
1
12
Order By: Relevance
“…Gardening has been associated with a healthier diet and lower BMIs (Alaimo et al 2008;Litt et al 2011;van den Berg et al 2010;Wakefield et al 2007;Zick et al 2013). Although participants in our study were overweight, the majority reported good to excellent health.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 57%
“…Gardening has been associated with a healthier diet and lower BMIs (Alaimo et al 2008;Litt et al 2011;van den Berg et al 2010;Wakefield et al 2007;Zick et al 2013). Although participants in our study were overweight, the majority reported good to excellent health.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 57%
“…Urban community gardens have a rich history in the United States of taking on conflicted political, social and historical meanings [8]. The ability to grow culturally appropriate food and maintain a cultural gathering space in community gardens has played a particularly important role amongst some immigrant populations [9][10][11][12]. Among native people, gardening can be used as a tool for decolonization [10].…”
Section: Introductionmentioning
confidence: 99%
“…Community gardens can also provide opportunities for positive intergenerational learning [10,[13][14][15] and positive interracial interaction [16]. By participating in community gardens, neighborhood residents also build organizing skills useful for other programs in the community [12].…”
Section: Introductionmentioning
confidence: 99%
“…Community gardens provide social benefits, such as the sharing of knowledge on food production with the wider community, and at the same time promote environmental awareness, stewardship of green space, and social equity through shared food production [6]. [10] Discusses that most gardeners in South-east Toronto community gardens were women, but men and children often attend and work in their plots. Regular tasks involved planting, weeding, watering and of course harvesting.…”
Section: Review Of Literaturementioning
confidence: 99%